N.A.A - Abdullah, Mohd Fadzrin; Pius, Priestly Evande; Lairis, Lorita; Jimmy Kua Yun, Desyree Olga; Cynta Vero, Annmarie (2014)
Nosotros Amor Autisms is a company that provides services to help the autisms people. Our business will be start on December. The services that we provide are such as training and therapy, counseling session with the parents, field trip, talk event, campaign and any other activities related to our business that can generate income. The location of our business is located at Api-Api centre apartment near Centre Point Mall, Kota Kinabalu. The reason why we chose this location is because it located in a city where there is lot of people come and go. We believe our business have potential compare to other business that similar to us due to our different types of services that we provide for our customer. We choose this services because of we want to increase people awareness regarding autisms especially in Sabah area and also want to help them in many ways as we could so that they can have better life in the future.